Defining 4G technology from the users perspective. - Frattasi, S. (IEEE Network : the magazine of global information exchange)
The ever-increasing growth of user demand, the limitations of the third generation of wireless mobile communication systems, and the emergence of new mobile broadband technologies on the market have brought researchers and industries to a thorough reflection on the fourth generation. Many prophetic visions have appeared in the literature presenting 4G as the ultimate boundary of wireless mobile communication without any limit to its potential, but in practical terms not giving any design rules and thus any definition of it. In this article we give a pragmatic definition of 4G derived from a new user-centric methodology that considers the user as the "cornerstone" of the design. In this way, we devise fundamental user scenarios that implicitly reveal the key features of 4G, which are then expressed explicitly in a new framework - the "user-centric" system - that describes the various level of interdependency among them. This approach consequently contributes to the identification of the real technical step-up of 4G with respect to 3G. Finally, an example of a potential 4G application is also given in order to demonstrate the validity of the overall methodology